The cult of the fox : power, gender, and popular religion in late imperial and modern China - Kang, Xiaofei, Ph.D (Columbia University Press, 2006)
For more than five centuries the shamanistic fox cult has attracted large portions of the Chinese population and appealed to a wide range of social classes. Deemed illicit by imperial rulers and clerics and officially banned by republican and communist leaders, the fox cult has managed to survive and flourish in individual homes and community shrines throughout northern China. In this new work, the first to examine the fox cult as a vibrant popular religion, Xiaofei Kang explores the manifold meanings of the fox spirit in Chinese society. Kang describes various cult practices, activities.